2015
DOI: 10.1177/1477750915622035
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment for providing clinical ethics consultation services in Tehran

Abstract: Introduction: One of the most important duties of hospital ethics committees is to provide medical ethics consultation to the staff and patients. This study was conducted with the aim of the needs assessment of the staff for optimal provision of medical ethics consultation services. Materials and methods: The data collection tool was a self-administered questionnaire. Hospital managers, chief nursing officers, ward managers, and head nurses of all hospitals affiliated with Tehran and Iran University of Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They found that the main reasons of the importance of ethical issues and ethical consultation attributed to the necessary information pertaining to informed consent, determination of patient's competence for decision-making, and decision-making for incompetent patients. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…They found that the main reasons of the importance of ethical issues and ethical consultation attributed to the necessary information pertaining to informed consent, determination of patient's competence for decision-making, and decision-making for incompetent patients. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…As there are few studies in the literature with similar aims, most of which using surveys [22][23][24], we adopted a qualitative approach, as this allowed us to deepen the participants' perspectives while also enabling some space for interpretations [25,26]. Semi-structured interviews were particularly suited for our goals, as they allow an indepth investigation, providing the opportunity to delve into the experiences and perspectives of stakeholders on clinical ethics issues [27].…”
mentioning
confidence: 99%